Esophageal High Pressure Zones: Effect of Perisophageal Structures on Esophageal Manometric Recording - G Bédard; A Pellicano; R Ste-Marie (Canadian Journal of Gastroenterology)
During the course of esophageal motility studies, short zones of elevated esophageal baseline pressure are occasionally noticed. The aim of this study is to determine their frequency and their cause. Among 77 consecutive esophageal manometries (group 1), 17 cases (22%) of ‘esophageal high pressure zones’ (EHPZs) were recorded. Thirty-three additional patients (group 2) were evaluated and 18 other cases of EHPZ were found; in the latter group, a miniature sound microphone was positioned on a carotid artery. When a high pressure zone was identified, the manometric catheter was immobilized; the patient underwent a chest x-ray, with the radiopaque marker imbedded in the catheter used to locate the thoracic structures adjacent to EHPZs. In both groups, indentations (pressure spikes) over the high pressure zones occurred synchronously with the patients’ radial or carotid pulse. Results suggest that EHPZs are caused by the compression and pulsations of vascular or cardiac periesophageal structures; the aortic arch is responsible for the manometric EHPZ when it is found between 10 and 14 cm above the lower esophageal sphincter whereas the left auricle is the cause of the EHPZ if it is located between 4 and 7 cm above the lower esophageal sphincter.